Balloon-occluded retrograde transvenous obliteration for bleeding gastric varices in a patient without a gastrorenal shunt - Saurabh Kumar; Apoorva Batra; Rinkesh Bansal; Reyaz Para (Society of Gastrointestinal Intervention, 2024)
Balloon-occluded retrograde transvenous obliteration (BRTO) is an endovascular technique frequently employed in the management of bleeding gastric varices among patients with portal hypertension. Bleeding from gastric varices is associated with higher mortality and morbidity compared to bleeding from esophageal varices, which are typically managed endoscopically. Compared to other interventions for gastric varices, BRTO is less invasive and can be performed in patients with poor hepatic reserve. The procedure involves occlusion of the outflow of the portosystemic shunt-often a gastrorenal shunt-using an occlusion balloon, followed by injection of a sclerosant into the varix. In this report, we describe a technique for accessing gastric varices that lack a gastrorenal shunt; this is accomplished using alternative shunt routes, such as the inferior phrenic vein. The reported approach is technically challenging due to the relatively small size of these shunts and the scarcity of cases documented in the literature regarding their use.